Sustainability of protected areas: Vulnerabilities and opportunities as revealed by COVID-19 in a national park management agency. (March 2021) - Smith, M. Kyle S.; Smit, Izak P.J.; Swemmer, Louise K.; Mokhatla, Mohlamatsane M.; Freitag, Stefanie; Roux, Dirk J.; Dziba, Luthando
Abstract: Protected areas (PAs) play a critical role in safeguarding Earth's biodiversity and contributing to human wellbeing. Maintenance of ecological intactness, financial viability and social relevance influence PA sustainability. We explore how COVID-19 and associated lockdown regulations influenced the sustainability of South Africa's largest PA management agency. Quantitative and qualitative information, sourced from ongoing monitoring, organizational reports, questionnaires and discussions with agency staff, were used to make sense of the challenges and opportunities. In the short term, lockdown regulations limited people's ability to access benefits from PAs with 50, 000 educational visits lost between April and June 2020 and recreational visits in access-controlled national parks decreasing by 96%. Consequently, tourism revenue dropped by 90% highlighting the fragility and risk of single primary income stream reliance. This resulted in loss of community development revenues and implementation of cost curtailment measures. Increased anxiety regarding health and job security impacted employee morale and complicated operational challenges. Navigating this period required good communication, re-prioritisation and adaptive responses by park managers. Whilst we report on short-term impacts and responses, lagged and longer-term impacts are anticipated. The pandemic highlighted the interconnectedness of people and ecosystems and the complex interdependencies between the sustainability principles which must be considered for increased PA resilience and sustainability. Highlights: The pandemic highlighted the interconnectedness of people and ecosystems, exposing both vulnerabilities and opportunities. The pandemic highlighted the risk and fragility of being reliant on one main income stream. Heightened concern and anxiety regarding health and job security impacted staff morale and wellness. Short term ecological benefits (reduced waste production and water usage) were experienced due to reduced tourism. Impacts stemming from the pandemic have been diverse, direct and indirect, operating at varying intensities and scales.